Curriculum Renewal in Legal Education : Final Report. - Kift, Sally; Butler, Des; Field, Rachael; McNamara, Judith; Brown, Catherine; Treloar, Cheryl (Office for Learning and Teaching, 2013)
There are 32 law schools in Australia and more than 20,000 law students (DEEWR, 2008). This is the final report from a project that focused on curriculum renewal of the final year of legal education and transition to professional practice. Project outcomes included: (1) articulated curriculum design principles for the final year (with adaptability potential to other disciplines), (2) a transferable model for an effective final year program, and (3) a final year in legal education forum and website. An iterative action learning methodology was employed in the project design phase, engaging national and international legal education experts, including ALTC teaching award winners, and two key representative bodies, the Australian Academy of Law, and the Australian Law Students' Association. Focus groups were conducted with students and recent graduates to obtain feedback on the developing draft principles and program. Preliminary research has suggested that the following three cornerstone curriculum objectives should inform the development of the final year principles and program: reflection, closure and transition.